„Chusta wiecznie zielona”. Pieta Teresy Ferenc. Studium wierszy - Katarzyna Janus (Język. Religia. Tożsamość, 2023)
The article attempts to interpret several of Teresa Ferenc’s poems included in the volume Pieta, published in 1981. The selected works combine the motifs of home, mother and the girl who is the author’s porte-parole. Written from the perspective of the trauma experienced in childhood: the burning of the family village and the death of her parents, we find numerous biblical allusions and cultural contexts, the explanation of which is the subject of this study. An attempt has been made to demonstrate the richness of the poetic imagery, the source of which can be traced back to extreme experiences.